Comparing Arab goal keepers performances with European goal keepers in the 2007 World Handball Championship. - Mansi, T. (World Congress of Performance Analysis of Sport VIII, 2008)
The last results showed the following: 1. Although the correlation coefficient between the average of height, weight, age and international experience from one side and the average saves from the other side was sometimes more than 50%, which is a high average, but it showed a statistical indication of zero, which means that the correlation is weak among these variables. This is because the sample was too small. Although there was not a big difference in height, wight, age and experince between Arab gaolkeepers and European ones, but the average saves of European goalkeepers were much better than that of Arabs because of the difference in training procedures and the existence of specialised trainers with very high experience and from early ages of goalkeepers. 2. There is no correlation between the average saves and the final rank of Arab teams sharing in the championship (the correlation coefficient was 0.18) which means that there was no considerable influence of the Arab goalkeeper on his team's rank negatively or positively. The Kuwaiti (Alfadly) was the best of Arabs although his team did not get a good status in the final ranking while the Tunisian team had the best position (the 11th) and if the Tunisian goalkeeper were better, then may be his team would have made a better place. Internationally the correlation coefficient was 0.42 which gives an indication of the superiority of European goalkeepers over the Arabs which was reflected on their teams' good ranking. 3. Skills of saving from the 6m line: the percentage of the Arab goalkeepers approximated that of the Europeans although there were some differences in saves, as (Alfadly) of Kuwait was the best with a percentage of (31). 4. The statistics showed a weakness of Arab goalkeepers in saving balls shot from the backward positions (34%) compared to that of Europeans (44.8%). That may be ascribed to the weakness of defense of Arab teams which permits the offenders to shoot freely and without any disturbance from defense compared to defense of European teams which had very powerful defenses and who use very successful and effective system of defense like (6:0) (the German, Polish, and Danish teams used this way and gained the first three ranks. This defense depends on tall players able to prvent shoots easily and they can disturb the offender while shooting from backward positions which weakens the effectiveness of the shoot and gives the goalkeeper an extra opportunity to save. Most Arab teams depended on (3:2:1) way of defense except Egyptian team and sometimes the Tunisian. 5. The statistics showed that there is no big difference between the levels of Arab and European goalkeepers in saving fast breaks balls where the player is face-to-face with the goalkeeper, 6. The best results of Arabs were to save penalty shoots, as the percentage was equal to that of Europeans (22%) and the Moroccan (Aledreesy) the first of Arabs (26%) and the German (Fritz) the first of all (37%) and which is a very high percentage. 7. To know the points of weakness and strength of goalkeepers in saving shot balls to different corners of target all shoots were analyzed and the statistics showed differences of percentages among goalkeepers of the study sample. The study showed a common weakness of dealing with shoots on the lower corners of target which agrees with the study of (Ragulj/ Srhoj, 2003). For Arabs, the weakness was very obvious compared to Europeans which is ascribed to to the weakness of dynamic movements of legs and the lack of elegance in general. Regarding shoots at upper corners the Arabs was a little better than Europeans in left corners and Europeans were a little better in right. The Europeans were better in dealing with shoots at the middle of target and to the right or left of the goalkeeper and these need a harmony of moving hands and legs at the same time and actively.